2020
DOI: 10.5812/ijem.101612
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practice Regarding Cardiovascular Diseases in Adults Attending Health Care Centers in Tehran, Iran

Abstract: Background: Studies on knowledge, attitude, and practice (KAP) can be valuable for public health to help in developing targeted educational programs and assessing the effectiveness of interventional programs. Objectives: This study was designed to determine the level of current knowledge, attitude, and practice (KAP) regarding cardiovascular diseases (CVDs), its risk factors, and symptoms in adults attending health care centers in Tehran Province. Methods: A cross-sectional study was performed using a self-adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
14
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 21 publications
14
14
3
Order By: Relevance
“…It seems reasonable to expect higher CVD knowledge scores in higher educated individuals, since more education can result in more exposure to information about diseases. Similar to some previous studies, which reported a significant association between age and CVD knowledge [ 25 , 28 ]; the current study showed that participants aged 40-49 years old were more knowledgeable about CVD risk factors compared to others. This is in line with other studies, which reported significant difference in CVD knowledge among different age groups [25] .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…It seems reasonable to expect higher CVD knowledge scores in higher educated individuals, since more education can result in more exposure to information about diseases. Similar to some previous studies, which reported a significant association between age and CVD knowledge [ 25 , 28 ]; the current study showed that participants aged 40-49 years old were more knowledgeable about CVD risk factors compared to others. This is in line with other studies, which reported significant difference in CVD knowledge among different age groups [25] .…”
Section: Discussionsupporting
confidence: 90%
“…Similar to some previous studies, which reported a significant association between age and CVD knowledge [ 25 , 28 ]; the current study showed that participants aged 40-49 years old were more knowledgeable about CVD risk factors compared to others. This is in line with other studies, which reported significant difference in CVD knowledge among different age groups [25] . This might be due to middle-aged people usually are more keen on getting medical care and having more intention to access physicians and knowing about CVD.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations